Leapfrogging of vortex rings - Ng, Yee Fatt (2017)
This report documents and discusses the findings of an experimental study conducted to shed light on the leapfrogging process of elliptic vortex rings, together with the associated interactions and flow structures. Planar laser induced fluorescence and time-resolved particle image velocimetry were employed to obtain both qualitative visualisations as well as quantitative flow measurements. Four cases of varying Reynolds number (Re=2000 and 4000) and time interval between the generation of the two rings (ΔT=0.05s and 0.2s) were investigated in two orthogonal planes along the major and minor axes of the elliptic orifice, and the results suggested that leapfrogging was more difficult to achieve for elliptic rings, as compared to circular ones, due to the additional inherent axis switching behaviour. A single passage was observed in both planes for Re=2000, ΔT=0.2s and Re=4000, ΔT=0.05s, although the passing ring dissipated soon after. Interestingly, for the case of Re=2000, ΔT=0.05s, the trailing vortices passed through successfully in one plane, but merged with the leading vortices in the other plane, demonstrating that the interaction was highly three-dimensional. It was also determined from the results for the case of Re=4000, ΔT=0.2s that the trailing ring unexpectedly bifurcated into two sub-rings under the combined influence of the self-induced velocity and the induced velocity from the leading ring. In a similar sense, partial bifurcation of the trailing ring could also explain the transient appearance of a counter-rotating vortex pair in two particular cases as well.